The Correlation Between Coping Mechanisms and Stress Levels with Smoking Habits Among Medical Students at Muhammadiyah University Semarang - Surya Oka Tanjung; Suprihhartini; Wijayanti Fuad; Rihadini (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
College students are particularly vulnerable to psychological stress or anxiety due to various factors such as academic demands, personality traits, environment, socio-cultural influences, and more. Smoking is a mental state influenced by one’s surroundings, leading to changes in behavior and emotions. Stress has become an inherent part of student life, driven by both internal and external pressures. Students employ different stress-coping strategies, namely problem-focused coping and emotion-focused coping. This study aims to examine the relationship between coping strategies, stress levels, and smoking behavior among medical students at Muhammadiyah University of Semarang. Using a quantitative observational analytic approach, the research was conducted in 2024 with 59 respondents selected through purposive sampling. The p-value for coping strategies was 0.411, while for stress levels, it was 0.043. These results indicate that H1 is accepted, showing a significant relationship between stress levels and smoking behavior. Stress levels can be a driving factor for smoking, highlighting a significant correlation between stress and smoking behavior